The situation of elderly people in Poland in the time of COVID-19 - Agnieszka Jasik; Jacek Pruszyński; Ewa Marcinowska-Suchowierska; Monika Puzianowska-Kuźnicka; Wojciech Stefan Zgliczyński (Wiedza Medyczna, 2022)
The aim of the article was, to present the situation of old people during the COVID-19 pandemic in Poland. The article has an illustrative character and is based on the available data. Authors starting from the presentation of basic demographic and epidemiological data, discussed such aspects of functioning of the elderly as, physical activity, economic, social, cultural and educational activity, and use of Internet resources, which were transformed due to the COVID-19 pandemic. In particular, isolation and protective measures such as distance, masks, handwashing and stay-at-home policies, and restrictions on congregation, have resulted in significant changes in the daily functioning of the old and have often led to increased social isolation, marginalisation and limited access to health care.